Adopsi Google Apps For Education Di Perguruan Tinggi: Sebuah Kolaborasi Real-Time Dosen Dan Mahasiswa - Intan Putri Cahyani (Balai Pengembangan SDM dan Penelitian Komunikasi dan Informatika (BPSDMP Kominfo) Banjarmasin, 2016)
Cloud-computing technology present as an impact of the changing cultural environment and competitive ecosystem of Higher Education in the world, including Indonesia. Cloud computing is actually a combination use of computer technology (